2014
DOI: 10.1016/j.jbiosc.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and selective analysis of widely targeted metabolomics using gas chromatography/triple-quadrupole mass spectrometry

Abstract: In metabolomics studies, gas chromatography coupled with time-of-flight or quadrupole mass spectrometry has frequently been used for the non-targeted analysis of hydrophilic metabolites. However, because the analytical platform employs the deconvolution method to extract single-metabolite information from co-eluted peaks and background noise, the extracted peak is artificial product depending on the mathematical parameters and is not completely compatible with the pure component obtained by analyzing a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…QqQMS-based MRM analysis can be used to easily distinguish single metabolite-derived peaks from co-eluted peaks and background noise, and it exhibits high sensitivity and a wide dynamic range compared with single-QMS [9], although gas chromatography/single-quadrupole mass spectrometry (GC/QMS) is very useful for comprehensive metabolite analysis [10]. In our previous study [4], GC/QMS was used to discover biomarker candidates for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…QqQMS-based MRM analysis can be used to easily distinguish single metabolite-derived peaks from co-eluted peaks and background noise, and it exhibits high sensitivity and a wide dynamic range compared with single-QMS [9], although gas chromatography/single-quadrupole mass spectrometry (GC/QMS) is very useful for comprehensive metabolite analysis [10]. In our previous study [4], GC/QMS was used to discover biomarker candidates for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To perform widely targeted metabolic profiling in the multiple reaction monitoring (MRM) mode, gas chromatography鈥搕riple quadrupole mass spectrometry (GC/QqQ-MS) was used for analyzing amino acids and organic acids, while analysis of intermediates of central metabolism such as sugar phosphates and cofactors was performed using reserved phase ion-pair liquid chromatography (RP-IP-LC)/QqQ-MS. Triple quadrupole mass spectrometer is suitable for metabolic profiling because of its high sensitivity and selectivity as well as its wide dynamic range that makes it possible to give accurate quantitative information [22,23]. Moreover, to obtain the absolute concentration of each metabolite, we used 13 C-labeled cell extracts as internal standards, a technique known to effectively reduce errors due to variations occurring in the analysis and sample processing [24].…”
Section: Introductionmentioning
confidence: 99%
“…37) Sawada et al reported widely targeted metabolome analysis using liquid chromatographtriple quadrupole-mass spectrometers (TQ-MS) by developing selected ion monitoring series of 378 metabolites. 38) Similar approaches are employed for the comprehensive analysis of lipids using liquid chromatograph-TQ-MS (lipidomics) 39) and analysis of primary metabolites using gas chromatograph-TQ-MS. 40) Although the number of measurable metabolites depends on the samples of interests, it has been reported that approximately 100-200 metabolites were usually analyzed by the widely targeted analysis. e widely targeted approach is now a productive and realistic strategy in metabolomics because the analysis could be performed using the more popular TQ-MS and default peak picking so ware developed by manufacturers.…”
Section: New Approach In the Metabolomics: Widely Targeted Analysismentioning
confidence: 99%